Host galaxy properties and environment of obscured and unobscured X-ray selected active galactic nuclei in the COSMOS survey - Bornancini, Carlos Guillermo (2020)
We analyse different photometric and spectroscopic properties of active galactic nuclei (AGNs) and quasars (QSOs) selected by their mid-IR power-law and X-ray emission from the COSMOS survey. We use a set of star-forming galaxies as a control sample to compare with the results. We have considered samples of obscured (HR > −0.2) and unobscured (HR < −0.2) sources including AGNs with LX < 1044 erg s−1, as well as QSOs (LX > 1044 erg s−1) with 1.4 ≤ z ≤ 2.5. We also study the typical environment of these samples, by assessing neighbouring galaxy number density and neighbour properties such as colour, stellar mass, and star formation rate. We find that the UV/optical and mid-infrared colour distribution of the different AGN types differ significantly. Also, we obtain most of AGNs and QSOs to be more compact when compared to the sample of SF galaxies. In general we find that the stellar mass distribution of the different AGN sample are similar, obtaining only a difference of ΔlogM = 0.3 dex (M☉) between unobscured and obscured QSOs. Obscured and unobscured AGNs and QSOs reside in different local environment at small (rp < 100 kpc) scales. Our results support previous findings where AGN type correlates with environment. These differences and those found in AGN host properties cast out the simplest unified model in which obscuration is purely an orientation effect.